# How do you solve using the completing the square method #0=3x^2-11x+6#?

##### 1 Answer

Apr 22, 2016

#x=3#

#x=2/3#

#### Explanation:

Given -

#3x^2-11x+6=0#

Divide each term by the coefficient of#x^2#

#x^2-11/3x+2=0#

Take the constant term to the right

#x^2-11/3x=-2#

Divide the coefficient of#x# by#2# and add the

thus received value to both sides after squaring it.

#x^2-(11/3xx1/2)x+(11/6)^2=-2+(11/6)^2#

#x^2-11/6x+121/36=-2+121/36#

#x^2-11/6+121/36=((-72)+121)/36=49/36#

Take square root on both sides

#(x-11/6)=+-sqrt(49/36)=+-7/6#

#x=7/6+11/6=(7+11)/6=18/6=3#

#x=-7/6+11/6=(-7+11)/6=4/6=2/3#